Diastereoselective Synthesis of an Industrially Relevant 4-Aminopentanoic Acid by Asymmetric Catalytic Hydrogenation in a Biphasic System Using Aqueous Sodium Hydroxide as Substrate Phase - Piscopo, Calogero G.; Gallou, Fabrice; Leitner, Walter; Franciò, Giancarlo (Synthesis, 2017)
A ’basic solution' for multiphase catalysis: The diastereoselective synthesis of a pharmaceutically relevant 4-aminopentanoic acid derivative has been studied using a chiral homogeneous catalyst in tailored biphasic reaction media. Different polar solvents were investigated as the stationary phase for the well-established Ru–Mandyphos catalyst in combination with aqueous NaOH as the substrate and product phase. Facile product isolation and effective recycling of the catalyst phase were demonstrated at gram-scale. In particular, up to 3200 turnovers have been achieved in seven repetitive batches with a diastereoselectivity of 87–96% using [EMIM][NTf2]/NaOHaq as the biphasic system.
Keywords: asymmetric hydrogenation; aqueous biphasic catalysis; ruthenium; Mandyphos; ionic liquid; catalyst immobilization